Stanowisko asystenta w prokuraturze — uwarunkowania prawne i praktyka - Tabernacka, Magdalena; Wolny, Mateusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
Regulations governing the structure of public authorities as well as the conditions of employment in public institutions should be designed in a manner to ensure their effectiveness. It is also necessary that the design of these regulations and conditions considers the findings of both law and social sciences such as sociology, organisation and management science and social psychology.The use of assistants in the Prosecutor’s Office is recommended given the need to ensure the rational division of work within this institution. This allows for effective and efficient use of the prosecutors’ time and efficient management of human resources in the Prosecutor’s Office. In fact, in Poland the problem is the insufficient number of assistants in the Prosecutor’s Office as well as the current legal regulation of the position of assistants which does not meet the expected criteria due to, among others, overly stringent requirements for the education of assistants. Similarly, the method of recruitment of assistants and their pay conditions prescribed by the regulations do not allow for the effective use of assistants in the structures of the Prosecutor’s Office.
Keywords: władze publiczne; prokuratura; racjonalność; asystent; sprawność